Defining openness: updating the concept of "open" for a connected world - Patrick McAndrew (Journal of Interactive Media in Education, 2010)
<!--[if gte mso 9]> 72 1024x768 <![endif]--><!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The release of free resources by the education sector has led to reconsideration of how the open approach implied by Open Educational Resources (OER) impacts on the educator and the learner. However this work has tended to consider the replication of standard campus based approaches and the characteristics of content that will encourage other institutions and individuals to join in (Wiley, 2006), rather than the approach to open learning itself and the changes that embracing openness imply. This paper will look at the experience of acting as an open university over 40 years, and how the understanding of the concept of openness has changed in the last 10 years by considering changes in how we view learners. The Open University was built on open concepts that allow learners to avoid barriers to study and successfully enabled more than 2 million people to experience formal higher education. However the openness that applied to the Open University did not cover all aspects that might be commonly assumed – such as free access, choice of start times, global availability. Offering free access to some material online has shown the impact that openness can have on learners and identified a range of behaviours that cluster around content driven and social driven approaches to learning. A combined view that considers the original values of open attached to The Open University alongside the emerging view from OER gives us the opportunity and driver for revising our view of openness and developing a position that helps bridge between formal and informal learning.